Nicotine Hypersensitivity in Inflammatory Dermatoses: A Systematic Review of Evidence for Nicotine as a Cutaneous Hapten - Sudan, Bernard J.L. (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Inflammatory dermatoses, such as seborrheic dermatitis (SD) and atopic dermatitis (AD), affect a significant portion of the population, yet their precise etiology often remains debated. Nicotine, a ubiquitous alkaloid primarily associated with tobacco but also present in certain plants and therapeutic products, has been proposed as a potential hapten capable of triggering hypersensitivity reactions manifesting as inflammatory skin conditions. This systematic review aimed to evaluate the existing evidence supporting the role of nicotine as a cutaneous hapten involved in the pathophysiology of inflammatory dermatoses. Methods: A systematic literature search was conducted using PubMed, Embase, and Google Scholar databases for studies published between January 2014 and December 2024. Keywords included "nicotine," "hapten," "allergy," "hypersensitivity," "contact dermatitis," "seborrheic dermatitis," "atopic dermatitis," "urticaria," and "skin reaction." Inclusion criteria encompassed original research (in vivo human studies, case reports/series, in vitro mechanistic studies) investigating nicotine's potential to elicit immune-mediated skin reactions consistent with a hapten mechanism. Data extraction focused on study design, population, nicotine source/exposure, diagnostic methods (patch test, prick test), and key findings related to hypersensitivity. Quality assessment was performed using appropriate tools (CARE guidelines for case reports, Joanna Briggs Institute checklists for other study types). Results: Following title/abstract screening and full-text review, six studies met the inclusion criteria. These included one cross-sectional prick-test study, two case reports detailing reactions to electronic cigarettes, one patch-test study, and two in vitro studies investigating mast cell responses. The prick-test study (N=30) reported positive reactions to nicotine in 20% of non-smokers and 7% of smokers, including one patient with SD. Case reports described eczematous reactions (perioral, hand dermatitis) associated with e-cigarette use. The patch test study indicated positive reactions in a subset of individuals exposed to nicotine patches. In vitro studies demonstrated nicotine-induced mast cell degranulation and mediator release (histamine), potentially inhibited by mast cell stabilizers. Conclusion: Consistent evidence from the included studies published between 2014-2024 suggests nicotine possesses the potential to act as a cutaneous hapten, capable of eliciting hypersensitivity reactions in susceptible individuals. Findings include positive diagnostic tests (prick/patch), clinical correlations (e-cigarette dermatitis), and plausible biological mechanisms involving mast cell activation. These reactions may contribute to or mimic inflammatory dermatoses like SD or contact dermatitis. Further robust clinical and mechanistic research is warranted to confirm these findings and clarify the prevalence and clinical significance of nicotine hypersensitivity in various dermatological conditions.